THE ROBUST ALTERNATIVE TO STANDARD VALIDITY APPROACH - Bosnar, Ksenija; Prot, Franjo (Annales Kinesiologiae, 2010)
The usual approach to criterion-related validity is developed under the canonical correlation model and is based on the maximization of the correlation of test results and the chosen criteria. The standard measures of validity are canonical correlation in the case of several test results and criteria, multiple correlation in the case of several test results and one criterion, and bivariate correlation in the case of one test and one criterion. In kinesiology, as well as some other disciplines, standard measures of validity are not always appropriate, being sensitive of the value of degrees of freedom. Therefore, the measures of validity based on the maximization of covariance of test results and chosen criteria proposed by Momirović et al. (1983), including robust canonical correlation analysis, robust regression analysis, robust discriminant analysis and redundancy analysis, may be more appropriate. The example in favour of this method of validation is presented.